(Essential Oil from The Twigs and Leaves of Sappuko (Leptospermum flavescens Smith) and Its Distillation Technique) - Sait, Salya; Hawani Lubis, Enny (Balai Besar Industri Agro, 1990)
The essential oil of Leptospermum flavescens leaves and twigs has been studied. The distillation techniques used were water distillation and water and steam distillation in order to determine the most suitable technique. The essential oil of the twigs and leaves are of the same type. Linalyl acetate, beta-terpineol, terpineol-4 and borneol are the major constituents of the oils and present in different quantities. The high content of linalyl acetate (34.44%) showed that the oil could become a new source of linalyl acetate. The result of the two distillation technique showed the significant difference in the leaves